Receptive performance and reading skills in children with hearing impairment (Research, Society and Development, 2022)
Introduction: Intervention, rehabilitation and audiological monitoring are essential to promote the development of communicative skills in children with hearing impairment leading to better conditions for academic performance, social inclusion and better quality of life. Objective: To analyze differences in the performance of children with hearing loss in receptive vocabulary and reading skills, when considering audiological and school characteristics. Method: Eighteen children with hearing loss, of both sexes, aged between 8 and 12 years were evaluated. For the analysis of receptive vocabulary, the PEABODYPPVT4 test was used, for reading performance, the One-Minute Reading tests - LUMP and the Reading Comprehension Test - TELCS test were used Results: 61.1% of the sample is composed of children with hearing loss hearing loss of moderate degree, 77.8% of the subjects have good audibility (SII ≥58), 61.1% of the analyzed subjects had a good level of vocabulary (≥70) and 67% of the sample presented results on average or above average in reading performance. Conclusion: Good audibility is related to the good vocabulary and reading performance of children with hearing impairment. Subjects with good performance in receptive vocabulary have good reading performance.